A core outcome set for all types of cardiac surgery effectiveness trials: a study protocol for an international eDelphi survey to achieve consensus on what to measure and the subsequent selection of measurement instruments. Issue 1 (December 2015) - Moza, A.; Benstoem, C.; Autschbach, R.; Stoppe, C.; Goetzenich, A.
Abstract Background Cardiovascular disease (CVD) is a major contributor to the burden of disease and the number one cause of death worldwide. From 1990 until today, more people died from coronary heart disease than from any other cause. CVD is regularly treated with minimally or non-minimally invasive off- or on-pump cardiothoracic surgery and several interventions related to the outcome of the surgical procedures have been evaluated in clinical trials, but heterogeneity in outcome reporting hinders comparison of interventions across trials and limits the ability of research synthesis. This problem is encountered with the introduction of core outcome sets (COSs), which should be measured and reported, as aminimum, in all clinical trials for a specific clinical field. Methods/design This study protocol describes the methods used to develop a COS for all types of cardiac surgery effectiveness trials. We aim to reach consensus onwhat to measure in an international three-round eDelphi exercise involving adult patients in need or after cardiothoracic surgery, cardiothoracic surgeons, cardiologists, anaesthesiologists, nursing staff and researchers with expertise in this particular field of medical research. Subsequently, outcome measurement instruments (how to measure) will be determined. Recommendations on COS development given by the Core Outcome Measures in Effectiveness Trials (COMET) Initiative and the Outcome Measures in Rheumatology (OMERACT) Initiative were followed. Discussion The proposed COS aims to provide methodological guidance for future cardiothoracic surgical trials to ensure the comparability of effects of interventions across studies and enable research synthesis. This does not imply that primary outcomes should always and exclusively be those of the COS. However, to ensure the comparability of results across trials, the outcomes included in this COS should be considered for inclusion besides measuring trial-specific clinical endpoints.